Effect of supplementary omega-3 fatty acids on pregnant women with complications and pregnancy outcomes: review from literature. (3rd July 2022) - Chowdhury, Mohammad Hasan; Ghosh, Susmita; Kabir, Md. Ruhul; Mamun, Md Abdullah Al; Islam, Md Shahedul
Abstract: Numerous benefits have been associated with omega-3 fatty acid consumption during pregnancy and the postpartum period, whether it is consumed in the diet with seafood or via supplements such as fish oil. This review primarily aimed to assess the current situation of the impact of omega-3 long-chain Poly Unsaturated Fatty Acid (PUFA) supplementation on the outcomes of pregnancy. The electronic search of Medline, PubMed, Public Library of Science (PLOS) and Google Scholar databases was carried out for papers from 01 February 1995 to 01 March 2017 using keywords such as "pregnancy, " "supplement, " "long-chain polyunsaturated fatty acids, " "omega 3 fatty acids, " and "clinical trials." Out of twenty-six studies, both observational and interventional, fourteen studies found the influence of omega 3 fatty acids during pregnancy or the early postpartum period on the duration of gestation and infant size at birth, preeclampsia, depression, and infant visual function and neurodevelopment have been reported. Omega 3 fatty acid intakes (both in terms of absolute amounts of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) and the ratio of these 2 fatty acids) varied widely in these studies, however, and no clear consensus exists regarding the effects of omega 3 fatty acids on any of these outcomes. Because of the potential importance of these fatty acids for pregnant or lactating women, fetus, and newborn infants and the limited data from clinical trials assessing the effect of these fatty acids on pregnancy and infant outcomes, additional research is required to better define optimal intakes of specific omega 3 fatty acids during these critical periods.